LEXICAL ACTIVATION IN HIGH AND LOW PROFICIENT BILINGUALS (ARABIC – ENGLISH) ON FREE NAMING TASK - Saddam H.M. Issa, Shyamala K.C (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The aim of this study was to investigate the differences in the lexical-semantic activation between the high and low proficient (Arabic-English) bilinguals by using picture naming task. Two main variables were measured extensively through this study which are reaction time and accuracy. The mean reaction time of the high proficient bilinguals was measured and compared with the mean reaction time of the low proficient. Also, the percentage of the correct responses was measured as well for both high and low proficient and compared with their performance in L1 and L2. Lexical-semantic organization for high proficient bilinguals and low proficient bilinguals was evaluated with picture naming experiment. Correlations were conducted in order to examine the performance of both HPB and LPB and their self- rating of their language skills. The results were discussed based on the bilinguals’ level of proficiency which is considered to be one of the ways of measuring lexical semantic organization.